Breast Device Surgery in Australia: Early Results from the Australian Breast Device Registry. Issue 10 (October 2021) - Vishwanath, Swarna; Pellegrini, Breanna; Parker, Emily; Earnest, Arul; Kalbasi, Saeid; Gartoulla, Pragya; Elder, Elisabeth; Farrell, Gillian; Moore, Colin; Cooter, Rodney D; Ahern, Susannah; McNeil, John J; et al.
Summary: Background: The Australian Breast Device Registry (ABDR) is a clinical quality registry designed to monitor the performance of breast devices; and the quality and safety of breast device surgery. Objective: To report on breast device surgery characteristics across Australia. Methods: Participants were registered patients in the ABDR from 2012 to 2018. Results are described using percentages, mean and median. Revision rates were calculated using survival analysis methods. Results: A total of 37, 603 patients were registered and had undergone reconstruction (post-cancer 15.1%, risk-reducing mastectomy 3.4% and developmental deformity 2.4%) or cosmetic augmentation (74.7%) procedures. The majority of breast implant devices were silicone filled with textured surface (reconstruction 74.0% and augmentation 64.0%). Sub-pectoral plane was the most common for both reconstruction (60.1%) and augmentation (76.6%) procedures. For reconstruction surgery, the most common surgical incision was previous mastectomy scar (44.0%) and inframammary (31.8%), and for augmentation, it was inframammary (83.4%). Intraoperative/postoperative antibiotic usage for reconstruction was 85.8% and augmentation was 89.4%. Revision incidence due to complication at 12 months post-cancer reconstruction was 5.1%, risk-reducing reconstruction 5.7% and developmental deformity implants 4.5%. Revision incidence due to complication at 12 months after augmentation procedure was 1.1%. Patient-reported outcome measures (PROMs) indicate high levels of satisfaction at 1 year for augmentation and reconstruction procedures. Conclusion: We report on early data from the ABDR and reflect on the uptake of the registry by surgeons and patients. The registry also benefits from international collaborative approaches to addressing challenges and is committed to facilitate international post-market surveillance.